The Effect of Educational Intervention of Infant Massage Through Android Application on The Growth and Development of Infants Aged 6 to 12 Months at Anny Rahardjo Main Clinic in 2022 - Rasumawati Rasumawati; Elin Puspita; Vivi Yuliani; Jusuf Kristianto (Syntax Corporation Indonesia, 2022)
Optimal growth and development is the result of the interaction of various interrelated factors, namely genetic, environmental and behavioral factors, as well as useful stimuli. One of stimulations that can be done is baby massage. Baby massage provides many benefits if it is done regularly and directed, so it is better for parents - who is always close to the baby, to do baby massage. In order for parents to be able to do baby massage properly, education is needed. Along with technological developments, the use of Android can be used as a medium for health educational information. Several studies show that the use of technology based on mobile applications and the internet has proven to be effective in increasing people's knowledge and behavior. This research was conducted by taking data on postpartum mothers who visited the Anny Rahardjo Main Clinic who were given baby massage education through an android-based application for the intervention group and the control group through baby massage guidelines. The design of this study used a Quasi Experimental Group with Pretest-Posttest Control Design. In the specified time period, the intervention group was given treatment. After the treatment was completed, measurements were made for both groups. The number of respondents was 60 people, consisting of 30 control groups and 30 intervention groups. The conclusion of this research using the baby massage android application showed positive results, with a guide that can be accessed whenever and wherever it makes parents do baby massage regularly and directed, so that there was a significant increase in the average of baby weight and baby development, and there was an influence of Baby Massage Educational Interventions through android applications on baby development.